Sports training and its role in achieving psychological compatibility among football players (a field study in some football clubs in the state of Bordj Bou Arreridj) - Ouchene, Bouzid (sports creativity, 2025)
Through our research, we have demonstrated the role of sports training in achieving psychological harmony among soccer players. The main and important idea that we drew from our research, based on the theoretical and applied studies we conducted using tools that reveal the phenomenon under study, After obtaining the results, we analyzed them and recorded the opinions of the sample individuals, which indicated that there is a lack of conflicts between coaches and players, which enhances athletic training processes. If there are any conflicts, most coaches confirmed that they use modern methods to resolve them, including direct dialogue and the intervention of other parties, such as the club president and club members. The most important conclusion we draw from analyzing the results of the questionnaire for the two samples is that sports training greatly achieves psychological harmony for players and develops physical activity, which has an impact on improving their psychological state, enabling them to improve their level of training and competition. This means developing the level of soccer for the better and bringing it in line with international levels and competencies.